Analysis of Flood Risk in the Lower Hydrographic Basin of the Río Negro (Argentina) - Garcia Bu Bucogen, Grethel (2024)
The recurrent floods in the lower hydrographic basin of the Río Negro (RN), documented since1899, have caused significant damage to the resident population settled in flood-prone areas, whose socio economic condition is unfavorable. The aim of this study was to analyze the risk associated with flood occurrences in this area by integrating the flood susceptibility level (hazard) of the study area and the vulnerability of the population.The risk analysis was derived from the algebraic overlay of hazard and vulnerability maps, developed accordingto criteria published by Renda et al. (2017). In the study area, floods are primarily caused by intense rainfall and winds, upstream water discharges from the Limay and Neuquén rivers, and interactions between increased upstream flow from the lower hydrographic basin of the RN and extreme meteorological events known as Sudestadas. Every certain period, such as every 2 years for winds exceeding 75 km/h and precipitation exceeding37 mm in 24 hours, as well as every 100 years for flows exceeding 4,000m3s−1, the occurrence of floods in the lower basin of the RN is expected to be derived from these events. Based on terrain characteristics and topography,41.7% of the lower RN basin area showed moderate to high susceptibility to flooding. INDEC data (2010)indicated that 51.0% of the population in the study area was vulnerable to floods due to unfavorable socio economic conditions. According to hazard and vulnerability analyses, 43.2% of residents in the lower RN basin lived in high-risk areas, with homes located near the riverbank and on the outskirts of the Viedma-Carmen de Patagones urban conglomerate, hence being the most vulnerable. The results obtained in this research showed the influence of the natural and anthropogenic factors on the occurrence of flood-related disasters in the lower hydrographic basin of the RN. In addition, they served as a preliminary study that will enable decision-makers to create better prevention and mitigation plans contributing to improving the quality of life of its inhabitants.